From hope to disappointment? Following the 'Taking Place' and 'Organisation' of hope in 'Building Back Better' from COVID-19. Issue 134 (August 2022) - White, Iain; Cretney, Raven
Abstract: Rapid economic stimulus in response to COVID-19, typically based on 'shovel-ready' infrastructure, has opened up new political spaces of hope to 'Build Back Better' and transform economies. This research seeks to link the public 'taking place' of hope, representing the aspirations of various groups for investment or change stimulated by this fund, with the less visible ways governments 'organise' hope, the expert, technical processes and rationalities that help determine which hopes become realised and why. Using the Aotearoa New Zealand 'shovel-ready' fund as a case study, and drawing upon press releases, media, Official Information requests, and Cabinet documents, we first provide a discourse analysis of the various government and non-government hopes that became attached to this stimulus. We then trace how these became translated into project proposals, before unpacking and analysing the urgent processes developed to assist political decision makers. While crises and hope can be positioned as having significant disruptive potential, we reveal how this was stifled by the technical processes and practices of the processual world enacted at the national scale, which was given significant power. Further, although public discourses reflected a plurality of multi-scalar and temporal hopes for investment, in practice the less visible organisation privileged a much more business-as-usual approach. Consequently, any government aspirations for transformation were rendered less likely due to the processes they themselves established. Overall, we emphasise the need for those committed to reform to bring technical processes and rational practices to greater prominence in order to reveal and challenge their power.